A hybrid electro-responsive SWNT/PEDOT: PSS-based membrane towards soft actuator applications. (February 2021) - Khan, Ajahar; Jain, Ravi Kant; Banerjee, Priyabrata; Alamry, Khalid A; Ghosh, Bhaskar; Inamuddin, ▪; Asiri, Abdullah M
The flexible soft actuators of conducting polymers can directly convert electrical stimulus into mechanical motions, which can be used for robotics and biomimetic applications. Herein, an electro-responsive membrane actuator based on poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonate), functionalized single-walled carbon nanotube was fabricated using solution casting method with poly(vinyl alcohol) as a base intermediate polymer membrane. The poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonate) was evenly ornamented onto the single-walled carbon nanotube/poly(vinyl alcohol) membrane (single-walled carbon nanotube/ poly(vinyl alcohol)/ poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonate)) surfaces through dip coating and verified by scanning electron and transmission electron microscopy analysis. The desirable bending response of the fabricated single-walled carbon nanotube/ poly(vinyl alcohol)/poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonate) membrane with time at different voltages and generated tip force makes it a promising material as a new-generation conductive polymer-based soft actuator. A permutation of the electrical conductivity, more surface area, and admirable electromechanical properties of the single-walled carbon nanotube/poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonate) components consequences in the composite electrode exhibited excellent actuation performance compared to the ionic polymer-metal composite actuators with Pt electrodes surface. The fabricated actuator membrane can be employed for artificial muscles, robotics, and other bio-mimetic applications.